Práticas Pedagógicas no ensino de crianças com autismo na perspectiva da Educação Inclusiva: um olhar do professor - Vecchia, Christiane Cordeiro Silvestre Dalla (2017)
Although the autism theme is part of the Brazilian scientific scenario, talking about children with autism is still a challenging task for researchers. Much is discussed in the social and behavioral scope of this theme, and little has been analyzed the pedagogical scope of inclusion of these children. In our study, we aimed to analyze the pedagogical practices from the teachers of elementary education from Guarapuava who act in the teaching of children with autism. The study comprised a descriptive qualitative research having as instruments interview and observation. The participants of research were four teachers from two state schools who attend children with autism in regular class, and two children included in these classes. It was decided to perform the analysis of the discourse of the results obtained through the interview and observation. Briefly, legislation on the inclusion of children with autism in regular classes is discussed; soon it addresses the cultural-historical theory of Vygotsky (1989, 1993, 1995, 2014) about the formation of thought and language in human development, turning these concepts for autism. The results indicate that the absence of speech in some children with autism does not represent absence of thought and learning. As regards the learning relations in autism according to the theory proposed by Vygotsky (1989, 1993, 1995, 2014), about the categories of mediation, zone of proximal development and levels of actual and potential development. It was possible to infer that in the process of teaching and learning child with autism, it is necessary to understand the instruments of mediation in the educational process. In addition, it is essential to discuss the zone of proximal development of child with autism, understanding social relationships, the levels of learning and the language of the children with autism. It was noted in loco the difficulties encountered by teachers to organize educational work aimed for child with autism. This research advances in order to emphasize the need for continuous training of teachers who work with children with autism in regular classes, since each child reacts differently to each mediating instrument. Thus, as mediators, teachers assume an excellent role in the process of teaching and learning child with autism in a regular classroom.